Knowledge, skills, and performance in biorisk management among allied health educators in the University of Perpetual Help System Jonelta - Baragona, Jamilah C.; Bermudo, Pedrito Jose V. (Technium Social Sciences Journal, 2023)
This descriptive-correlational study determined the relationship between the health educators’ knowledge, skills, and performance in biorisk management in the University of Perpetual help System Jonelta. The study probed the predictive ability of knowledge and skills of the health educators’ performance in biorisk management. The results of the study served as basis in developing a training program on biorisk management that was common and applicable to all allied health educators. The study, which was conducted from November 2022 to April 2023, involved 199 health educators of the University as respondents. The study results revealed that the respondents’ level of knowledge on biorisk management was very high (x̅ = 3.27); level of skills was high (x̅ = 2.93), and level of performance was high (x̅ = 3.08). Significant relationships were found between the respondents’ level of knowledge and level of skills; between level of knowledge and level of performance; and between level of skills and performance in biorisk management along principles and policies, assessment, safety measures, waste management, and personnel protective equipment (p<0.01). Further, knowledge along safety measures (p=.007<.05), waste management (p=.0071<.05), and level of skills along personal protective equipment(p=.029<.05), and the combination of all skills (p=.007<.05) were found to be significant predictors of performance in biorisk management. It was concluded that the allied faculty members of UPHSL are highly cognizant of the effective management of risks posed by working with infectious agents and toxins; they are competent, trained, and experienced in various aspects of biorisk management in health education settings; and they enforce the use of personal protective equipment (PPE) in a health education setting and are skilled in managing the proper disposal of biological waste, among others. Likewise, the higher is their level of knowledge, the higher the level of skills on biorisk management and level of performance in biorisk management; and the higher their level of skills, the higher is the level of performance in biorisk management. Moreover, knowledge on safety measures and waste management; and skills on personal protective equipment and the combination of all the skills on principles and policies, assessment, safety measures, waste management, and personal protective equipment are predictors of performance in biorisk management